PENGARUH KEKERASAN VERBAL TERHADAP SELFACCEPTANCE ANAK DI PANTI ASUHAN AL-ANSHOR KECAMATAN TENAYAN RAYA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the influence of verbal violenceagainst self-cceptance children in the orphanage Al-Anshor District Tenayan Raya Pekanbaru. The population in this research was 4-6 years old, 39 children and 6 early childhood caregivers at Al-Anshor orphanage Tenayan Raya Pekanbaru District, samples of these studies as many as 39 early childhood children and 6 caregivers were taken using saturated sampling methods. The data collection techniques used are observations. Analytical techniques use a test scale and analysis of statistical methods of linear regression simplified with the SPSS for Windows Ver. 22 program. Based on the results of the hypothesis test obtained there is how much influence of verbal violence against self-acceptance children in the orphanage Al-Anshor District Tenayan RayaPekanbaru. It can be found from the value of the koleration coefficient of 0.616 which lies at the range of 0.60-0799. The level of influence of verbal violence against selfacceptance children at Al-Anshor orphanage of Tenayan Raya Pekanbaru District in a strong category against self-acceptance children.Key words: Self-Acceptance, Verbal abuse